PROBLEMS OF SURGICAL TREATMENT OF ACUTE PURULENT-NECROTIC PARAPROCTITIS - Baysariyev Shovkat Usmonovich (Research Focus International Scientific Journal, 2025)
This article analyzes the clinical outcomes of 367 patients who underwent surgery at the Proctology Department of Clinic No. 1, Samara State Medical University, between 2010 and 2023. Among them, 26 patients (7.08%) were diagnosed with purulent-necrotic forms of the disease, while 341 patients (92.92%) had perirectal tissue damage of aerobic etiology. The average age of the patients was 53.1 ± 4.9 years. All patients underwent a comprehensive diagnostic assessment including clinical evaluation, digital rectal examination, rectoscopy, transabdominal and transrectal ultrasonography, computed tomography, and bacteriological analysis of wound discharge. Emergency surgical intervention was performed in all cases. The study results demonstrated that timely and radical surgical treatment, supplemented with appropriate antibacterial and detoxification therapy, led to full recovery.